Pengaruh Pengelolaan Dana Zakat Profesi BAZNAS Kabupaten Brebes terhadap Optimalisasi Penyaluran Dana Zakat - Muslikhun, Ahmad; Muhyiddin, Asep; Aziz, Rohmanur (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to determine the effect of planning, organizing, implementing, and supervising the collection of professional zakat funds and the distribution of zakat funds to the poor in Baznas, Brebes Regency. The method used is descriptive quantitative method. The results of this study indicate that the level of application of the management system for the collection and distribution of zakat funds is quite good. The results of the analysis and testing of the descriptive test hypothesis obtained a percentage value of 77%, in the simple linear regression test the Fcount value of 0.355,035 was greater than the Ftable value of 1.987, and obtained a significance value in the product moment correlation test of 0.000 < from 0.05, which means that the two variables have a relationship and Pearson's value of 0.885 which is in the interval 0.80-1,000 in the category of very strong influence level.